Performance Analysis of Spectral Amplitude Coding Methods in Fiber Optical Communication System - Abusale, Wahhab Abdulrazzaq; Ilhan, Haci; Karabulut, Muhammet Ali (SPRINGER, 2023)
This study analyzes optical code division multiplexed access system coding with two different types of spectral amplitude coding (SAC): Double Weight (DW) codes and Multiple Diagonal (MD) codes. These two encoding types differ in code structure and channel bandwidth length (the number of wavelengths representing the channel's bandwidth), as well as Q-Factor, BER, and MAI values. This study analyzes systems with different number of users over single-mode optical fiber and presents a comparison of both. DW codes have a shorter length of code than MD codes, and although this technique can generate unique code words for each user, it will break the system using MD encoding. This is another reason to increase bandwidth for MD codes.
Keywords: BER; DW; Eye height; MD; Optical fiber communication; Q-Factor; DIVISION MULTIPLE-ACCESS; OCDMA SYSTEMS; CODE FAMILY; Telecommunications